Harriet Jacobs Gets a Hearing - Crawley, Ashon (Current Musicology, 2012)
What can one hear in confinement, and how can that hearing be connective lineament? In her grandmother’s crawlspace for seven years—compressed as a means to escape, confined with access only to shallow air as a means to flight—Harriet Jacobs was both discarded and discardable. What did it mean to be discarded, for discardable materiality to bespeak an ontological condition? What can we learn from Jacobs’s existence in the crawlspace, of her throwing herself into claustrophobic conditions to stage her eventual scurrying away? Her discarded body bodies forth socially and a sociality. What is the social life—as opposed to the social death—of the discarded? Her existence in that crawlspace, as an object that was thrown and thrown away, is cause for celebration. Harriet Jacobs knew something about black performance as a mode of sociality that is still reproduced today. Sound, for Harriet Jacobs, was an important resource for allowing her thriving, even in the most horrific of conditions.